Climate variability and change: perceptions, experiences and realities - Rao, K.P.C.; Oyoo A (Tudor Rose, 2012)
Farming in the semi-arid tropics, where climatic conditions are marginal and highly variable, is a risky enterprise. The main source of this risk is the variability in rainfall that occurs at many different timescales, ranging from seasons to years to decades and beyond. Farmers operating under these conditions make decisions based on their perceptions and experiences gained from several years of keen observation and practice in the field. However, perceptions are influenced by many factors, both real and subjective. For agriculture, factors like farm productivity, crop, market and local preferences, capacity to invest, willingness to take risks and soil quality play an important role. While the role and significance of some of these factors on productivity and profitability can be perceived more easily due to their relative predictability, extreme variability in climate and the random nature of that variability makes it difficult for farmers to accurately perceive trends in climate. In the absence of detailed measurements, perceptions can be biased and unreliable. Climate information can play an important role in helping farmers better understand this variability and its associated risks, and enhancing their decision-making for effective risk management.